Alpha‐lipoic acid: An inimitable feed supplement for poultry nutrition. Issue 1 (26th April 2017) - Sohaib, M.; Anjum, F. M.; Nasir, M.; Saeed, F.; Arshad, M. S.; Hussain, S.
Summary: Alpha‐lipoic acid (ALA) is a multifunction antioxidant that is produced in small amount by cells as well as its dietary provision facilitates fatty acid mobilization, energy expenditure as well as can scavenge free radicals in poultry birds. It exists in oxidized as well as reduced form, characterized by growth promoting, anti‐inflammatory, antioxidative, immunostimulatory, and hypocholesterolemic properties when fed as dietary supplement to farm animals particularly chicken birds. Recently, several studies reported that dietary supplementation of ALA can influence growth performance indicators, immunological, biochemical characteristics, lipid metabolism, and oxidative stress as well as increase antioxidant potential and storability of poultry meat and meat products. Accordingly, this paper adds the reviews and discusses the outcomes of studies documenting the effect of lipoic acid dietary fortification on growth performance, biochemical, and immunological characteristics as well as the effects on lipid peroxidation of fresh meat and meat‐based products. Furthermore, this paper also describes the possibilities of utilization of ALA as a feed additive in poultry nutrition to improve the growth performance of poultry as well as meat quality of resultant chicken birds.